The Beatles : get back [videorecording (DVD)] - McCartney, Paul; Starr, Ringo; Lennon, John, 1940-1980; Harrison, George, 1943-2001 (Disney, 2022)
Directed by filmmaker Peter Jackson, this is a three-part documentary series that takes audiences back in time to the band's intimate recording sessions. The documentary showcases the warmth, camaraderie, and creative genius that defined the legacy of the iconic foursome, and is compiled from over 60 hours of unseen footage shot in January 1969 (by Michael Lindsay-Hogg) and more than 150 hours of unheard audio, all of which has been brilliantly restored. Also featured, for the first time in its entirety, is The Beatles' last live performance as a group, the unforgettable rooftop concert on London's Savile Row, as well as other songs and classic compositions featured on the band's final two albums, Abbey Road and Let It Be.